PENERAPAN SWEDISH MASSAGE UNTUK MENURUNKAN TEKANAN DARAHPADA PENDERITA HIPERTENSI DI PUSKESMAS PAMPANG MAKASSAR - Kristina Wisrance; Akbar Asfar; Andi Mappaanganro; Brajakson Siokal (Jurnal Kesehatan, 2025)
BackgroundHypertension, or high blood pressure, is one of the most common public health problems worldwide. It is known as the "silent killer" because it often has no obvious symptoms, but it can lead to serious complications such as heart disease, stroke, kidney failure, and premature death if not properly treated. Method:The research method was a case study of a hypertension patient. The intervention was administered for three consecutive days, each lasting 30 minutes. Blood pressure was measured before and after the therapy.Swedish massage Nursing Care ResultsThe analysis results show that Swish massage therapy is effective in lowering blood pressure, indicating a significant decrease in blood pressure. Before the intervention, the patient's blood pressure was in the grade I–II hypertension category (174/98 mmHg). After the intervention,Swedish massage, blood pressure decreased to 145/88 mmHg accompanied by a more relaxed patient condition. ConclusionThe conclusion of this study is that Swedish massage is effective in lowering blood pressure through the mechanisms of muscle relaxation, blood vessel vasodilation, parasympathetic system stimulation, and stress hormone reduction. Swedish massage can be recommended as a safe, easy, and beneficial non-pharmacological complementary therapy in controlling hypertension in primary health care.